Fatty Acid Composition and Contents of Fish of Genus Salvelinus from Natural Ecosystems and Aquaculture - Michail I. Gladyshev; Alexander A. Makhrov; Ilia V. Baydarov; Stanislava S. Safonova; Viktor M. Golod; Sergey S. Alekseyev; Larisa A. Glushchenko; Anastasia E. Rudchenko; Vladimir A. Karpov; Nadezhda N. Sushchik (Biomolecules, 2022)
Fatty acids (FA) of muscle tissue of Salvelinus species and its forms, S. alpinus , S. boganidae , S. drjagini , and S. fontinalis , from six Russian lakes and two aquacultures, were analyzed. Considerable variations in FA compositions and contents were found, including contents of eicosapentaenoic and docosahexaenoic acids (EPA and DHA), which are important indicators of fish nutritive value for humans. As found, contents of EPA+DHA (mg·g −1 wet weight) in muscle tissue of Salvelinus species and forms varied more than tenfold. These differences were supposed to be primarily determined by phylogenetic factors, rather than ecological factors, including food. Two species, S. boganidae and S. drjagini , had the highest EPA+DHA contents in their biomass and thereby could be recommended as promising species for aquaculture to obtain production with especially high nutritive value. Basing on revealed differences in FA composition of wild and farmed fish, levels of 15-17-BFA (branched fatty acids), 18:2NMI (non-methylene interrupted), 20:2NMI, 20:4n-3, and 22:4n-3 fatty acids were recommended for verifying trade label information of fish products on shelves, as the biomarkers to differentiate wild and farmed charr.